Village Infernos and Witches' Advocates : Witch-Hunting in Navarre, 1608-1614. - Homza, Lu Ann (Iberian encounter and exchange, 475-1755., 2021)
"Between 1608 and 1614, thousands of witchcraft accusations were leveled against men, women, and children in the northern Spanish kingdom of Navarre. The Inquisition intervened quickly but incompetently, and the denunciations continued to accelerate. As the phenomenon spread, children began to play a crucial role. Not only were they reportedly victims of the witches' harmful magic, but hundreds of them also insisted that witches were taking them to the Devil's gatherings against their will. Presenting important archival discoveries, Lu Ann Homza restores the perspectives of illiterate, Basque-speaking individuals to the history of this shocking event. combines new readings of the Inquisitional evidence with fresh archival finds from non-Inquisitional sources, including local secular and religious courts, and from notarial and census records. Expanding our understanding of this witch hunt as well as the history of children, community norms, and legal expertise, Village Infernos and Witches' Advocates is a must-read for scholars of the Spanish Inquisition and the history of witchcraft in early modern Europe"--